1984
DOI: 10.1254/jjp.35.451
|View full text |Cite
|
Sign up to set email alerts
|

Parallelism between Avoidance-Suppressing and Prolactin-Increasing Effects of Antipsychotic Drugs in Rats

Abstract: Temporal changes in the avoidance responses and serum prolactin levels were investigated for a 360 min period after s.c. administration of antipsychotic drugs such as chlorpromazine (2 mg/kg), prochlorperazine (2 mg/kg), haloperidol (0.035 mg/kg), droperidol (0.03 mg/kg), YM-09151-2 (0.005 mg/kg) and sulpiride (80 mg/kg) in rats. Male adult rats of the Wistar strain were trained under a continuous lever-press avoidance schedule (Sidman type) to observe avoidancesuppressing effects of the drugs. The avoidance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…The hospital record provided neuroleptic dose and benzodiazepine doses given. Neuroleptic dose was converted to chlorpromazine equivalents 38,39 and benzodiazepine dose to diazepam equivalents 40 …”
Section: Methodsmentioning
confidence: 99%
“…The hospital record provided neuroleptic dose and benzodiazepine doses given. Neuroleptic dose was converted to chlorpromazine equivalents 38,39 and benzodiazepine dose to diazepam equivalents 40 …”
Section: Methodsmentioning
confidence: 99%
“…The hospital record provided information for measures of two emergency treatment interventions: number of hours in seclusion and neuroleptic dose given. Neuroleptic dose was converted to chlorpromazine equivalents 28,29 . Hospital records provided length of stay in PES (which serves as an acute inpatient unit usually for stays of less than 24 hours) and length of total hospital stay.…”
Section: Methodsmentioning
confidence: 99%
“…A report by Kondo et al (2000) showed that prolactin levels increase about 3-fold (on average) with age in male chimpanzees. However, this report does not specify how long the blood sample was taken after administering ketamine and the dopamine D 2 -like antagonist droperidol, and both of these agents increase prolactin (Puri, Puri & Anand Kumar, 1981; Hayashi & Tadokoro, 1984; Schettini et al, 1989; Rizvi et al, 2001; Hergovich et al, 2001). For comparison, human males have no significant differences in prolactin levels from prepubescence to adulthood (Guyda & Friesen, 1973; Aubert, Grumbach & Kaplan, 1974; Lee, Jaffe & Midgley, 1974; Ehara, Yen & Siler, 1975; Finkelstein et al, 1978).…”
Section: Discussionmentioning
confidence: 99%